The children act [videorecording (DVD)] - Eyre, Richard, 1943-; Thompson, Emma; Tucci, Stanley; Chaplin, Ben; McEwan, Ian (Lionsgate, 2018)
As her personal life falls apart, a judge has to decide a difficult case where religious parents of a 17-year-old boy suffering from leukemia refuse to allow the hospital to perform a life-saving blood transfusion.